Anterior cruciate ligament reconstruction and cartilage contact forces—A 3D computational simulation. Issue 10 (December 2015) - Wang, Lianxin; Lin, Lin; Feng, Yong; Fernandes, Tiago Lazzaretti; Asnis, Peter; Hosseini, Ali; Li, Guoan
Abstract: Background: Clinical outcome studies showed a high incidence of knee osteoarthritis after anterior cruciate ligament reconstruction. Abnormal joint kinematics and loading conditions were assumed as risking factors. However, little is known on cartilage contact forces after the surgery. Methods: A validated computational model was used to simulate anatomic and transtibial single-bundle anterior cruciate ligament reconstructions. Two graft fixation angles (0° and 30°) were simulated for each reconstruction. Biomechanics of the knee was investigated in intact, anterior cruciate ligament deficient and reconstructed conditions when the knee was subjected to 134 N anterior load and 400 N quadriceps load at 0°, 30°, 60° and 90° of flexion. The tibial translation and rotation, graft forces, medial and lateral contact forces were calculated. Findings: When the graft was fixed at 0°, the anatomic reconstruction resulted in slightly larger lateral contact force at 0° compared to the intact knee while the transtibial technique led to higher contact force at both 0° and 30° under the muscle load. When graft was fixed at 30°, the anatomic reconstruction overstrained the knee at 0° with larger contact forces, while the transtibial technique resulted in slightly larger contact forces at 30°. Interpretation: This study suggests that neither the anatomic nor the transtibial reconstruction can consistently restore normal knee biomechanics at different flexion angles. The anatomic reconstruction may better restore anteroposterior stability and contact force with the graft fixed at 0°. The transtibial technique may better restore knee anteroposterior stability and articular contact force with the graft fixed at 30° of flexion. Highlights: Neither the anatomic nor the transtibial anterior cruciate ligament reconstruction can completely restore normal biomechanics and articular contact force. The anatomic reconstruction may better restore anteroposterior stability and articular contact force with the graft fixed at 0° of flexion. The transtibial technique may better restore anteroposterior stability and articular contact force with the graft fixed at 30° of flexion.